CHERISHING OF THE UKRAINIAN LANGUAGE ABROAD - Duplak, Mykola (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article of Mykola Dupliak "Cherishing of the Ukrainian Language in Foreign Countries" refers to Lemko-Ukrainians who were forcibly taken to the north of Poland in 1947 to the so-called "Ziemie Odzyskane" and settled, dispersed them there in different areas so that they could not communicate with each other. . In order to polonize, Ukrainian children were deprived of the opportunity to study in their native language. However, most Ukrainian families still raised children in the Ukrainian spirit, preserved and studied the Ukrainian language. The author of the article tells how they raised children in his family, how he improved his own knowledge of the Ukrainian language independently, how his family moved to the United States of America, but also retained his Ukrainia identity. The author himself, through persistent self -education and work on himself, became one of the best experts in the mother tongue, thus he has been the editor of the Ukrainian weekly magazine "People's Will" in the United States, a consultant on speech culture in the Ukrainian magazine "Borysten". The purpose of the article. The article aims to show what difficulties Ukrainians in Poland, and then in distant America, had to overcome to maintain their identity, to preserve their native Ukrainian language. Research methodology. The article is built on the author’s own memoirs, which describe in detail the disenfranchised position of Lemko-Ukrainians, whose villages did not even have schools, a political situation in Lemkivshchyna after the Second World War, the deportation of Lemkos to Ukraine, and then to the northern territory of Poland. Those children, who wanted to know the Ukrainian language had to look for private ways of studying it, as the author himself did. Research results. The article shows on the example of the life of the author and his family desperate efforts of Ukrainians to maintain their identity and native language in a foreign language environment The scientific novelty of the article does not raise doubt since there were no such publications in the Ukrainian discourse that would show how Ukrainians retain and cherish their mother tongue in foreign lands.